Content Analysis of Risk Communication on Three Instagram Accounts of Provincial Health Offices in Indonesia During the Covid-19 Pandemic. (March 2022) - Shellanabilla, C.; Ismail, A.; Pramesthi, A.A.; Muhadzib, M.A.; Werdani, K.E.; Arifah, I.; Wijayanti, A.C.; Kusumawati, Y.; Junaedi, F.; Darmawan, E.S.; Jati, S.P.; Taki, S.; et al.
Abstract : Purpose: This study aims to analyze risk communication related to Covid-19 conducted by three Provincial Health Offices on their Instagram account. This research used descriptive quantitative method with a content analysis approach. Methods & Materials: The study was limited to the first 6-month-period of crisis moments in Indonesia from March to August 2020. The unit of analysis were postings of three accounts of the Provincial Health offices on Instagram. The population of this study were 970 postings and the samples were 792 postings related to Covid-19 that were chosen using purposive sampling technique. The instruments were coding instrument which were organized in a codebook. It consists of 7 main codes based on previous established study. The main codes were modified into 20 subcodes. The code and subcodes were tested by 4 coders using Krippendorff 's alpha (α) for its intercoder' s reliability. All categories were reliable (α>0.8). Results: The results showed that risk communication varied among three Provincial Health Offices and in some area needs improvement. The most types of postings were are in the form of posters with caption or posters only (66.5%) and the least types of postings were video or Instagram TV (0.1%). Some of the messages' target were made to provide information (46.6%) and only a few were aimed at building public trust. The most targeted audiences were general public (91.6%), while the least targeted audiences were organizations (0.1%). Covid-19 content in the form of behavior change education was the most uploaded postings (46.2%) while government policies related to covid-19 were very limited in the postings (3.5%). Most of the postings cited websites and or social media (54.9%) for references and scientific journals (0.3%) were the least cited. The most widely used message intonation was with positive intonation (84.8%). Conclusion: Instagram plays as an important complementary tool for risk communication by the government. Provincial Health Offices may add more postings that will improve public trust to the government in managing and handling Covid-19 problems and to improve the public engagement, understanding, and responses to Covid-19.